People consensus in the use of ethnomedicinal plants for conservation in and around purbachal modern town, dhaka (Bangladesh Journal of Botany, 2024)
The present study aims to determine the consensus on the use of ethnomedicinal plants available in and around the Purbachal modern town area for conservation. The data were collected through nine field trips during the year 2023 using a semi-structured questionnaire, followed by interviews showing plants, mentioning checklists, field interviews, a market survey, and participant observations. The study recorded 185 medicinal plant species under 78 families, which have been used through 673 formularies to treat 48 complaints in 13 disease categories. Among the medicinal plants, trees were 49%, herbs 27%, shrubs 16%, and climbers 8%. Leaf (31%) is the major plant part used, followed by fruit (19%), bark (6%), stem (11%), root (6%), seed (9%), whole plant (5%), flower (3%), and others. Cuts and wounds attained the highest FIC value and were treated by 18 medicinal plant species. Among the most cited species are Cynodon dactylon (L.) Pers. and Cissus quadrangularis L.. According to Fl value, Ocimum tenuiflorum L. is a culture-bound species because it has been used for respiratory tract complaints only. The most commonly cited species of medicinal plants are Ocimum tenuiflorum L., Cynodon dactylon (L.) Pers., Justicia adhatoda L., Terminalia arjuna (Roxb. ex DC.) Wight & Arn. and Coccinia grandis (L.) Voigt. Based on observations and interviews with local people, a good number of threats were detected for medicinal plant species. To conserve medicinal plants in Purbachal modern town, plantations in each sector should have some native medicinal trees including Terminalia arjuna (Roxb. ex DC.) Wight & Arn., Azadirachta indica A. Juss., Phyllanthus emblica L., Litsea glutinosa (Lour.) Robinson, Syzygium cumini (L.) Skeels, Sterculia villosa Roxb. ex Sm., Terminalia bellirica (Gaertn.) Roxb., Alstonia scholaris (L.) R.Br., Moringa oleifera Lamk., Holarrhena pubescens Wall. ex G.Don, Bombax ceiba L., Aegle marmelos (L.) Corr., Tamarindus indica L., Zanthoxylum rhetsa (Roxb.) DC., Toona ciliata M. Roem., Cassia fistula L., Flacourtia jangomus (Lour.) Raeusch., Garcinia cowa Roxb., Baccaurea ramiflora Lour., Ficus racemosa L., Ficus benghalensis L., Aphanamixis polystachya (Wall.) R.N. Parker, Milliusa velutina (DC.) Hook.f. & Thomson, Spondias pinnata (L.f.) Kurz, Oroxylum indicum (L.) Benth. ex Kurz, Neolamarckia kadamba (Roxb.) Bosser, and Elaeocarpus serratus L., so that town dwellers can find them easily.Bangladesh J. Bot. 53(3): 577-588, 2024 (September)